2020
DOI: 10.21037/jtd-20-230
|View full text |Cite
|
Sign up to set email alerts
|

The mutation profiles of cell-free DNA in patients with oesophageal squamous cell carcinoma who were responsive and non-responsive to neoadjuvant chemotherapy

Abstract: Background: The aim of this study was to evaluate the clinical value of plasma cell-free DNA (cfDNA) mutation profiles in patients with oesophageal squamous cell carcinoma (OSCC) who received neoadjuvant chemotherapy. Methods: Twenty-two OSCC patients received neoadjuvant chemotherapy and were divided into two groups according to their response to the therapy. Fifteen patients were in the responsive group, and seven patients were in the non-responsive group. The blood samples were collected, and the plasma cfD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Moreover, Zhang et al explored the cfDNA mutation signature of patients with ESCC who were responsive and nonresponsive to neoadjuvant chemotherapy (NAC). It was illustrated that the driver gene molecular mutation burden (MMB) of the responsive group was significantly higher than that of the non-responsive group and that the plasma cfDNA MMB and CNVs may be used to predict the response of ESCC patients to NAC (42). Likewise, a study with a cohort of patients with early breast cancer who received NAC found that ctDNA levels after two cycles of NAC predict the local tumor response to NAC treatment, and positive baseline ctDNA is significantly associated with worse DFS and OS (43).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Zhang et al explored the cfDNA mutation signature of patients with ESCC who were responsive and nonresponsive to neoadjuvant chemotherapy (NAC). It was illustrated that the driver gene molecular mutation burden (MMB) of the responsive group was significantly higher than that of the non-responsive group and that the plasma cfDNA MMB and CNVs may be used to predict the response of ESCC patients to NAC (42). Likewise, a study with a cohort of patients with early breast cancer who received NAC found that ctDNA levels after two cycles of NAC predict the local tumor response to NAC treatment, and positive baseline ctDNA is significantly associated with worse DFS and OS (43).…”
Section: Discussionmentioning
confidence: 99%
“…Nineteen studies reported on the PFS of the ctDNA [14,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. As the range of HR between these studies was 1.21 to 18.70, a significant association was observed between ctDNA-positivity in EC patients and the poorer PFS.…”
Section: Correlation Between Ctdna and Pfsmentioning
confidence: 99%
“…It is speculated that a tumor bearing a higher TMB level may be highly immunogenic as it is likely to harbor more neoantigens. These neoantigens can then be targeted to a higher degree by activated immune cells capable of inducing an anti-tumor immune response, which would result in a good clinical prognosis [ 37 , 41 ]. This increase in neoantigens occurs because TMB is believed to be a good indicator of the number of immunogenic neopeptides displayed on the surface of tumor cells, which influences patient response to ICIs [ 38 ].…”
Section: Tumor Mutational Burdenmentioning
confidence: 99%
“…These miRNAs profiles may also serve as lead targets for new treatments [ 20 ]. The miRNA expression profiling of OSCC is distinct from that of oesophageal adenocarcinoma [ 41 ]. Some studies analysing the expression profiles of miRNA using unsupervised hierarchical clustering demonstrated that these profiles can be used to classify different types of oesophageal cancer due to the significant differences in the miRNA profiles between these oesophageal disease groups [ 44 ].…”
Section: Micrornasmentioning
confidence: 99%